The Difference of Anatomical Pathology Test Result on Combined and Separate Laboratory Activity of Histologi-Anatomical Pathology - Pertiwi, Dwi Bhakti; Afifah, Zulaika Nur; Subariyanti, Briandani (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Introduction: Laboratory activity is one of the learning process in that aims to help students to achievethe learning objectives of a Block. The combined laboratory activity of Histology-Anatomical Pathology had been conducted on 2014. This combined laboratory activity was affectedthe outcome of learning process, in this case wasthe test result. The studyaims to compare Anatomical Pathology test result on combined and separate laboratory activity of Histology-Anatomical Pathology. Methods: The research was a cross-sectional observational analytical. It had been done at Faculty of Medicine Sebelas Maret University on November, 2015. Subjects of this research weresecond and third year students. The data was collected by stratified random sampling. The Anatomical Pathology test result that will be compared is the Anatomical Pathology test result on Musculoskeletal Block. The data was analyzed byMann-Whitney test. Results: The result of Mann-Whitney test showed the value of p= 0.237 (p > 0.05) means insignificant statistically between Anatomical Pathology test result on combined and separate laboratory activity of Histology-Anatomical Pathology. Conclusions: There was no difference of Anatomical Pathology test result on combined and separate laboratory activity of Histology-Anatomical Pathology in Faculty of Medicine Sebelas Maret University. Keywords: Test Result, Laboratory Activity, Anatomical Pathology